TAVI Procedure Accesses: Our Experience and Comparison of Transapical Versus Transfemoral Routes - Glib I. Yemets; Volodymyr I. Horbatiuk; Andrii V. Maksymenko (Ukrainian Journal of Cardiovascular Surgery, 2024)
There is no denying the fact that surgical aortic valve replacement has been considered as the “gold standard” of treatment for patients with aortic stenosis (AS). However, approaches are changing. A particularly influential event was the first successful transcatheter aortic valve implantation (TAVI) from an antegrade transseptal approach in 2002.The aim. To evaluate the results of TAVI performed using transapical and transfemoral access in patients over 60 years of age with severe AS.Materials and methods. This single-center study was performed at the Ukrainian Children’s Cardiac Center in the period from 2016 to 2024. The study included 105 consecutive patients with a confirmed diagnosis of severe AS. All the patients met eligibility criteria, received a full package of basic and additional examinations and, based on the decision of the heart team led by a cardiac surgeon, were verified for the TAVI procedure from the appropriate access: transfemoral access in group 1 (n = 54 patients), transapical access in group 2 (n = 51 patients). Patients who had previously undergone aortic valve replacement were excluded from the study.Results. All the patients were verified as high surgical risk patients according to the STS Adult Cardiac Surgery Risk Calculator, EuroSCORE II, ASA scales. Intraoperative mortality was 0.95% (n = 1). The postoperative period of hospital stay (from the time of operation to discharge) was 11.13 ± 10.45 days (from 3 to 54) in group 1 and 12.65 ± 11.68 days (from 0 to 71) in group 2. The procedure was performed under general anesthesia in both groups. Duration of the operation was 147.59 ± 113.46 minutes (from 110 to 810) in group 1, and 168.31 ± 93.61 minutes (from 76 to 690) in group 2. Early outcomes, assessed by echocardiography and aortography, were satisfactory in all the patients. In group 1, minimal paravalvular insufficiency was detected in 92.6% (n = 50), moderate paravalvular insufficiency was observed in 7.4% (n = 7) patients. In group 2, minimal deficiency was found in 90.2% (n = 46), moderate in 9.8% (n = 5) patients.Conclusions. Early and long-term postoperative outcomes were satisfactory in both groups. There was no statistically significant difference between the groups in the level of complications. However, the pattern of complications differed between the groups: the transfemoral group had a lower rate of postoperative bleeding and cerebrovascular disorders, while the transapical group had a lower rate of pacemaker implantation and prosthesis repositioning.